Dynamic Stabilization of Simple Fractures With Active Plates Delivers Stronger Healing Than Conventional Compression Plating. Issue 2 (February 2017) - Bottlang, Michael; Tsai, Stanley; Bliven, Emily K.; von Rechenberg, Brigitte; Kindt, Philipp; Augat, Peter; Henschel, Julia; Fitzpatrick, Daniel C.; Madey, Steven M.
Abstract : Objectives: Active plates dynamize a fracture by elastic suspension of screw holes within the plate. We hypothesized that dynamic stabilization with active plates delivers stronger healing relative to standard compression plating. Methods: Twelve sheep were randomized to receive either a standard compression plate (CP) or an active plate (ACTIVE) for stabilization of an anatomically reduced tibial osteotomy. In the CP group, absolute stabilization was pursued by interfragmentary compression with 6 cortical screws. In the ACTIVE group, dynamic stabilization after bony apposition was achieved with 6 elastically suspended locking screws. Fracture healing was analyzed weekly on radiographs. After sacrifice 9 weeks postsurgery, the torsional strength of healed tibiae and contralateral tibiae was measured. Finally, computed tomography was used to assess fracture patterns and healing modes. Results: Healing in both groups included periosteal callus formation. ACTIVE specimens had almost 6 times more callus area by week 9 ( P < 0.001) than CP specimens. ACTIVE specimens recovered on average 64% of their native strength by week 9, and were over twice as strong as CP specimens, which recovered 24% of their native strength ( P = 0.008). Microcomputed tomography demonstrated that compression plating induced a combination of primary bone healing and gap healing. Active plating consistently stimulated biological bone healing by periosteal callus formation. Conclusions: Compared with compression plating, dynamic stabilization of simple fractures with active plates delivers significantly stronger healing. Abstract : Supplemental Digital Content is Available in the Text.